Stopped-light nanolasing in optical magic-angle graphene - K. L. Tsakmakidis (Nature Nanotechnol., 2021)
An optical analogue of magic-angle twisted graphene bilayer gives rise to rigorously stopped light, which coupled with gain allows for a new type of a nanolaser with remarkable figures of merit.